2020
DOI: 10.2337/dc19-1769
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Metformin in the GRADE Cohort: Effect on Glycemia and Body Weight

Abstract: We evaluated the effect of optimizing metformin dosing on glycemia and body weight in type 2 diabetes. RESEARCH DESIGN AND METHODSThis was a prespecified analysis of 6,823 participants in the Glycemia Reduction Approaches in Diabetes: A Comparative Effectiveness Study (GRADE) taking metformin as the sole glucose-lowering drug who completed a 4-to 14-week (mean 6 SD 7.9 6 2.4) run-in in which metformin was adjusted to 2,000 mg/day or a maximally tolerated lower dose. Participants had type 2 diabetes for <10 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
5
0
4
Order By: Relevance
“…The efficacy of metformin is dose-dependent [ 19 , 21 ], with maximal benefits observed at the upper limits of the recommended daily dosage [ 21 - 23 ] and a minimum fully effective dose of 1.5 g/day [ 22 ]. Nevertheless, the real-world dosage patterns of metformin have been so far poorly investigated [ 10 , 11 ], particularly in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of metformin is dose-dependent [ 19 , 21 ], with maximal benefits observed at the upper limits of the recommended daily dosage [ 21 - 23 ] and a minimum fully effective dose of 1.5 g/day [ 22 ]. Nevertheless, the real-world dosage patterns of metformin have been so far poorly investigated [ 10 , 11 ], particularly in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…These observations corroborate the previous study findings indicating effectiveness of high-dose metformin in achieving HbA1c reduction and weight reduction. 11 , 24 The landmark UK Prospective Diabetes Study (UKPDS) evaluated a median daily metformin dose of 2550 mg/day in people with newly diagnosed T2DM and reported a median HbA1c of 7.4% compared with 8.0% in the conventional group. 8 In the Diabetes Prevention Program study, during the unblinded follow-up, weight loss was significantly greater in the metformin group compared to the placebo group (−2.0 vs −0.2%, P < .001).…”
Section: Discussionmentioning
confidence: 99%
“… 24 While 2500 mg is considered the maximum dose of metformin, most providers will prescribe up to 2000 mg daily because increasing the dose from 2000 mg to 2500 mg had minimal impact on HbA1c with a slight increase in adverse events. 24 A recent study showed that optimizing metformin to the 2000 mg daily or the maximum tolerated lower dose improves glycemia in type 2 diabetes, 25 confirming that the efficacy of metformin is dose dependent.…”
Section: Metformin: Clinical Use In Type 2 Diabetesmentioning
confidence: 97%